T Cell Epitope Discovery in the Context of Distinct and Unique Indigenous HLA Profiles - Hensen, Luca; Illing, Patricia T.; Rowntree, Louise C.; Davies, Jane; Miller, Adrian; Tong, Steven Y. C.; Habel, Jennifer R.; van de Sandt, Carolien E.; Flanagan, Katie L.; Purcell, Anthony W.; Kedzierska, Katherine; Clemens, E. Bridie (Frontiers in Immunology, 2022)
CD8+ T cells are a pivotal part of the immune response to viruses, playing a key role in disease outcome and providing long-lasting immunity to conserved pathogen epitopes. Understanding CD8+ T cell immunity in humans is complex due to CD8+ T cell restriction by highly polymorphic Human Leukocyte Antigen (HLA) proteins, requiring T cell epitopes to be defined for different HLA allotypes across different ethnicities. Here we evaluate strategies that have been developed to facilitate epitope identification and study immunogenic T cell responses. We describe an immunopeptidomics approach to sequence HLA-bound peptides presented on virus-infected cells by liquid chromatography with tandem mass spectrometry (LC-MS/MS). Using antigen presenting cell lines that stably express the HLA alleles characteristic of Indigenous Australians, this approach has been successfully used to comprehensively identify influenza-specific CD8+ T cell epitopes restricted by HLA allotypes predominant in Indigenous Australians, including HLA-A*24:02 and HLA-A*11:01. This is an essential step in ensuring high vaccine coverage and efficacy in Indigenous populations globally, known to be at high risk from influenza disease and other respiratory infections.